P‐Azidophenylarsenoxide: An Arsenical "Bait" for the In Situ Capture and Identification of Cellular Arsenic‐Binding Proteins. (10th October 2016) - Yan, Xiaowen; Li, Jinhua; Liu, Qingqing; Peng, Hanyong; Popowich, Aleksandra; Wang, Zhixin; Li, Xing‐Fang; Le, X. Chris
Abstract: Identification of arsenic‐binding proteins is important for understanding arsenic health effects and for developing arsenic‐based therapeutics. We report here a strategy for the capture and identification of arsenic‐binding proteins in living cells. We designed an azide‐labeled arsenical, p‐azidophenylarsenoxide (PAzPAO), to serve bio‐orthogonal functions: the trivalent arsenical group binds to cellular proteins in situ, and the azide group facilitates click chemistry with dibenzylcyclooctyne. The selective and efficient capture of arsenic‐binding proteins enables subsequent enrichment and identification by shotgun proteomics. Applications of the technique are demonstrated using the A549 human lung carcinoma cells and two in vitro model systems. The technique enables the capture and identification of 48 arsenic‐binding proteins in A549 cells incubated with PAzPAO. Among the identified proteins are a series of antioxidant proteins (e.g., thioredoxin, peroxiredoxin, peroxide reductase, glutathione reductase, and protein disulfide isomerase) and glyceraldehyde‐3‐phosphate dehydrogenase. Identification of these functional proteins, along with studies of arsenic binding and enzymatic inhibition, points to these proteins as potential molecular targets that play important roles in arsenic‐induced health effects and in cancer treatment.